Microglial Regulation of Neuropathic Pain - Makoto Tsuda; Takahiro Masuda; Hidetoshi Tozaki-Saitoh; Kazuhide Inoue (Elsevier, 2013)
Neuropathic pain is a highly debilitating chronic pain state that is a consequence of nerve injury or of diseases such as diabetes, cancer, infection, autoimmune disease, or trauma. Neuropathic pain is often resistant to currently available analgesics. There is a rapidly growing body of evidence indicating that signalings from spinal microglia play crucial roles in the pathogenesis of neuropathic pain. After peripheral nerve injury, microglia transform to reactive states through the expression of various genes such as cell-surface receptors (including purinergic receptors) and proinflammatory cytokines that enhance synaptic transmission in dorsal horn neurons. Inhibiting function or expression of these microglial molecules strongly suppresses pain hypersensitivity to innocuous mechanical stimuli (tactile allodynia), a hallmark symptom of neuropathic pain. A recent study also reveals that the transcription factor IRF8 (interferon regulatory factor 8) is a critical regulator of the nerve injury-induced gene expression in microglia. The present review article highlights the recent advances in our understanding of spinal microglia in neuropathic pain. Keywords:: microglia, purinergic signaling, transcription factor, neuropathic pain, spinal cord